Smartphone APPlications in the clinical care and management of Rheumatic Diseases - Salaffi, Fausto; Farah, Sonia; Di Carlo, Marco (Acta Biomedica Atenei Parmensis, 2018)
Background: Rheumatic diseases (RDs) are the most common cause of severe long-term pain and physical disability, affecting hundreds of millions of people around the world. Smartphones technology have the potential to become an important tool that rheumatologist can employ in the clinical care management of RD. Methods: Research of the published literature on the principle electronic databases available as Ovid MEDLINE, Health Technology Assessment Database, Embase, and PsycINFO was conducted, and the studies evaluated eligible were reviewed. Results: Our search produced 120 results from which 47 eligible articles were identified reporting studies of smartphone apps for patients with RD. All examined feasibility and five assessed the efficacy of a smartphone intervention for clinical care management. Conclusions: It has been demonstrated a strong evidence for the feasibility of using smartphone to enhance care of patients with RD. Based on the available literature and our personal experiences, we consider useful the development of some mobile phone apps, to simplify and assist the rheumatologist during his clinical practice. Still remains limited data on the efficacy of such interventions.